SIFAT PAPAN PARTIKEL DARI LIMBAH KAYU GELAM (Melaleuca cajuputi) PADA BERBAGAI KADAR PEREKAT PVAC - Muhammad Reza Pahlevi; Lusita Wardani; Siti Hamidah (Jurnal Sylva Scienteae, 2019)
ABSTRACT. The research aim to analyze physical and mechanical properties of particle board from gelam wood waste which is influenced by PVAc adhesive, and this research is useful to provide information on the use of gelam wood waste through the manufacture of particle board products using PVAc adhesive with various adhesive grades. The research design which is applicated, is Completely Randomized Design (RAL) with 4 treatments and 3 repetition, so it has 12 boards as its sample. The parameters that I calculate in this research are moisture content, density and firmness (MoR). The results of the research explained the values of each parameter are: moisture content 14.94% - 16.35%, density 0.74g / cm3 - 0.85g / cm3 and bending firmness (MoR) 3,31kg / cm3 - 14, 28kg / cm3. Thus the particle board density meets the standards of SNI 03-2105-2006 and JIS A 5803.Keywords: Gelam; PVAc; Particle Board.ABSTRAK. Penelitian ini bertujuan untuk menganalisis sifat fisik dan mekanik papan partikel berbahan limbah kayu gelam yang dipengaruhi oleh kadar perekat PVAc, dan penelitian ini bermanfaat untuk memberikan informasi penggunaan limbah kayu gelam melalui pembuatan produk papan partikel dengan berbagai kadar perekat PVAc. Rancangan penelitian yang dipakai adalah Rancangan Acak Lengkap (RAL) yang menerapkan 4 perlakuan serta 3 pengulangan, sehingga total sampel berjumlah 12 papan. Parameter yang saya hitung yaitu kadar air, kerapatan dan keteguhan lentur (MoR).Hasil uji menunjukkan nilai masing-masing parameter yaitu: kadar air 14,94% - 16,35%, kerapatan 0,74g/cm3 – 0,85g/cm3 dan keteguhan lentur(MoR) 3,31kg/cm3 – 14,28kg/cm3 . Jadi, kerapatan papan partikel yang diuji telah memenuhi standar SNI 03-2105-2006 dan JIS A 5803.Kata kunci: Gelam; PVAc; Papan Partikel